Instagram Users Reception of User-Generated Aesthetics on Ankayama’s Instagram Account - Kayla Vanessa Immanuel; Lady Joanne Tjahyana; Daniel Budiana (Journal of Content and Engagement, 2025)
"User-Generated Aesthetic" refers to a vernacular form of "User-Generated Content." Ankayama, a content creator, embodies the User-Generated Aesthetic pattern. By doing so, Ankayama upholds the value of eco-beauty and presents content with a high aesthetic appeal. The emergence of this new term in content creation signifies a shift in acceptance, making it an intriguing area of study. This research employs Stuart Hall's reception analysis method and is descriptive. The findings indicate that Instagram users hold a dominant and negotiating position in response to Ankayama's User-Generated Aesthetic and a dominant position in Ankayama's aesthetics and content education. This influence results from personal factors such as personality, culture, motivation, and experience of the informant, Ankayama's brand involvement in content, content style, and the originality of the creator.